From Barren Fields to Grape Vineyards - Neelakantan, K. S. (Indian Forester, 2000)
The land use change taking place in the foothills of the Western Ghats of Megamalai Reserve Land in Theni District of Tamil Nadu, has to be seen to be believed. This watershed was treated under the Tamil Nadu Afforestation Programme in 1997-1998. Due to the soil and moisture conservation structures undertaken in the watershed, the ground water potential has improved. Abandoned bore wells are being used now and grape cultivation in about 100 acres which was fallow till recently is in progress. This has been documented and presented.